Qualitative Analysis of Management Information Systems on Employee Performance at CV Gudang Madu Sumatera - Abdul Kahar; Alhudori; Nurlaila (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
This study aims to conduct a qualitative analysis of the impact of management information systems on employee performance at CV Gudang Madu Sumatera, Jambi City. Management information systems provide a framework that involves hardware, software, and human resources in collecting, managing, and disseminating relevant information within the organization. Employee performance reflects individual efforts to achieve company goals. This study employs a qualitative approach by collecting data through interviews, observations, and document analysis. The research participants consist of employees from various departments and levels within the company. The collected data is analyzed using thematic analysis techniques to identify patterns, themes, and relationships emerging from the interviews, observations, and documents analyzed. The results of the analysis indicate that this qualitative analysis provides deep insights into the influence of management information systems on employee performance at CV Gudang Madu Sumatera. Management information systems have a significant impact on employee performance at CV Gudang Madu Sumatera, Jambi City. These findings highlight several important factors, such as the ease of information access, the speed of decision-making, data integration, and management support for the use of management information systems. These factors contribute to improved employee performance in terms of efficiency, productivity, and job satisfaction.